Um rio entre diversas temporalidades: o Jaguaribe a partir da construção do Açude Orós (1958 –1964) - Silva, Kamillo Karol Ribeiro e (2018)
The Orós Dam is the central point of this study about Jaguaribe River, trying to understand how it is seen, read and written, counted and experienced before and after this technical intervention made in the early 1960s. This paper aims to deal with this main issue: how will it be possible to perceive the Jaguaribe River after the construction of the Orós Dam? What changes and permanencies can be found in this trajectory? The developments and issues to be problematized from this proposal depart from the concrete and symbolic journeys already made by myself and others in the waters of the Jaguaribe River. Taking, at first, as reference of this text a natural element - the river, I seek to approach WORSTER (1991, p. 199) when he says that "environmental history deals with the role and place of nature in human life"1, to understand the reason for this research. In this text, the construction of the Orós dam, its history and trajectory, will be understood from an experience of feelings, such as absence, hope, fear and deception, seen as components of a microcosm reflecting a larger structure than at that time it was the country and the world. Finally, as it approaches the raw material of the historical discipline, this research has a final inquiry: from the construction of the Orós dam, what temporalities does the Jaguaribe inaugurate for the subjects involved in this plot? It occurs that, in the geographical and spatial context of this study we will see that with time, the Jaguaribe has been transmuted from the interventions that it underwent. These interventions may be the dams built along its bed, the fences that isolated it from its populations, the irrigated perimeters served by it, it seems, we will verify that another river emerged: one with a source and a mouth in the future, a concrete hope for a future, whose profile to be achieved is to contribute to the region becoming what it never was. Based on these themes, we will try to understand the Jaguaribe River connected to the construction of the Orós Dam, thinking about the history of drought and water in Ceará, in the light of reflections on the theory of environmental history, nature and culture studies and also contribute to the studies of social history of science and technique, while investigating such a relationship (river-weir) in the folds of time.